2023
DOI: 10.1128/jb.00080-23
|View full text |Cite
|
Sign up to set email alerts
|

OprF Impacts Pseudomonas aeruginosa Biofilm Matrix eDNA Levels in a Nutrient-Dependent Manner

Abstract: Many pathogens form biofilms, which are bacterial communities encased in an extracellular matrix that protects them against antibacterial treatments. The roles of several matrix components of the opportunistic pathogen Pseudomonas aeruginosa have been characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Thus, the contributions of OmpT and OmpA to biofilm formation could be conditional and governed by environmental stress responses. In P. aeruginosa , the major OMP, OprF, is an abundant matrix protein and promotes or represses biofilm formation depending upon growth conditions ( 62 , 63 ). OprF interacts with surface-exposed lectin LecB, which binds P. aeruginosa exopolysaccharide Psl, thereby promoting biofilm matrix assembly and stability through increased retention of cells and exopolysaccharides in biofilms ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the contributions of OmpT and OmpA to biofilm formation could be conditional and governed by environmental stress responses. In P. aeruginosa , the major OMP, OprF, is an abundant matrix protein and promotes or represses biofilm formation depending upon growth conditions ( 62 , 63 ). OprF interacts with surface-exposed lectin LecB, which binds P. aeruginosa exopolysaccharide Psl, thereby promoting biofilm matrix assembly and stability through increased retention of cells and exopolysaccharides in biofilms ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that eDNA can form PsI-eDNA fiber webs with extracellular polysaccharide PsI ( Byrd et al., 2009 ), and in addition, eDNA can interact with Pel ( Jennings et al., 2015 ; Jennings et al., 2021 ) to protect eDNA from degradation by DNase I. Due to the important position of eDNA in biofilm EPS ( Kanampalliwar and Singh, 2020 ; Peng et al., 2020 ; Dawson et al., 2021 ; Cassin et al., 2023 ), more and more scholars have begun to pay attention to drug development targeting eDNA. Previous studies have reported the effects of natural compounds ( Meto et al., 2020 ), synthetic novel substances ( Patel et al., 2020 ) and amino acids ( Gnanadhas et al., 2015 ) on eDNA in P. aeruginosa biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, OMVs have long been believed to interact with eDNA in the biofilm matrix (119)(120)(121). Though no direct interaction with OprF has been proposed, loss of the protein was shown to affect overall eDNA production under some conditions (122). Thus, the role of OprF in OMV-matrix interaction is an area ripe for deeper investigation, and a new understanding that OprF in OMVs adopts a different conformation than OprF in cells provides a new wrinkle to be further explored.…”
Section: Discussionmentioning
confidence: 99%